Współczesna poezja lubuska wobec niemieckiej przeszłości regionu (na wybranych przykładach) = Contemporary Poetry of Ziemia Lubuska against the German Past of the Region (Chosen Examples ) - Sobczak, Marika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The central idea of presented article is the remembering German heritage of Ziemia Lubuska, whichhas been like subject forgetting and excluding in political since 1989. The forms of German historyare to feature by regional poets (Krzysztof Fedorowicz, Kazimierz Furman, Mieczysław Morawski,Barbara Trawińska, Marek Lobo Wojciechowski, Jerzy Beniamin Zimny) for examples: commonplacemaps, memory landscapes, anthropology of things and problem of roots trees and plants to plantedtrees by Germans. This collection of poems is subject to reinterpretation, which is connected withnew perspective of research problem and is taking the foregoing into account and relations with human and things.
Keywords: poezja lubuska; poezja religijna; stosunki polsko-niemieckie; literatura polska - tematyka - 21 w.